2023
DOI: 10.1007/s40572-023-00400-z
|View full text |Cite
|
Sign up to set email alerts
|

Dairy and Plant-Based Milks: Implications for Nutrition and Planetary Health

Abstract: Purpose of Review Dairy milk products are dominant in the market; however, plant-based milks are gaining prominence among USA consumers. Many questions remain about how plant-based milk products compare to dairy milk from a nutrition, public health, and planetary health perspective. Here, we compare the retail sales, nutrient profiles, and known health and environmental impacts of the production and consumption of dairy and plant-based milks and identify knowledge gaps for future studies. For our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…Another example of a trade-off is that dairy may have higher levels of certain nutrients compared to plantbased milks, in some cases due to fortification; however, this study and many others indicate that dairy's environmental footprint is significant − both in absolute terms and compared to most plant-based milk. 61 Our findings have implications for other high meatconsuming countries with frequent or increasing use of weight-loss diets. The current global trajectory of agricultural production exceeds food system environmental targets.…”
Section: (A) (B)mentioning
confidence: 73%
“…Another example of a trade-off is that dairy may have higher levels of certain nutrients compared to plantbased milks, in some cases due to fortification; however, this study and many others indicate that dairy's environmental footprint is significant − both in absolute terms and compared to most plant-based milk. 61 Our findings have implications for other high meatconsuming countries with frequent or increasing use of weight-loss diets. The current global trajectory of agricultural production exceeds food system environmental targets.…”
Section: (A) (B)mentioning
confidence: 73%
“…Fortification can also play an important role for new foods meant to provide alternatives to those foods that have traditionally been manufactured from animal ingredients. Systematic reviews have demonstrated that few meat-and-dairy-alternative products are fortified with nutrients typically found in the corresponding animal foods (vitamin D, vitamin B 12 , iron, calcium, and zinc) and could manifest as nutritional inadequacies over time if used exclusively as substitute products [ 36 , 37 , 38 , 39 , 40 , 41 ]. This has also become more important in view of the consistent and ongoing discussion over the increase in the proportion of plant-based foods (including plant protein foods) in diets to enhance environmental sustainability and to decrease chronic-disease risk [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Milk and its products are one of the main sources of nutrients in People's Daily life (Ramsing et al., 2023). Milk fat is dispersed in the form of lipid droplets in milk, which are easily absorbed and can provide people with rich nutrients and energy (Zhao et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of the MAP2K2 gene is related to cell proliferation and apoptosis (Yan et al, 2022). Since the MAP2K2 gene may be a factor affecting dairy cow mammary epithelial cells, and it is regulated by miR-2285f, the study of cell Milk and its products are one of the main sources of nutrients in People's Daily life (Ramsing et al, 2023). Milk fat is dispersed in the form of lipid droplets in milk, which are easily absorbed and can provide people with rich nutrients and energy (Zhao et al, 2023).…”
Section: Effects Of Mir-2285f On Fat Milk Marker Pparg Suppresses Lip...mentioning
confidence: 99%